1998
DOI: 10.1034/j.1399-3054.1998.1030101.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of ambient levels of solar UV‐A and UV‐B radiation on growth of cv. New Red Fire lettuce

Abstract: The influence of solar UV‐A and UV‐B radiation at Beltsville, MD, USA, on growth of Lactuca sativa L. (cv. New Red Fire lettuce) was examined during early summer of 1996 and 1997. Plants were grown from seed in plastic window boxes covered with Llumar to exclude UV‐A and UV‐B, polyester to exclude UV‐B, or tefzel (1996) or teflon (1997) to transmit UV‐A and UV‐B radiation. After 31–34 days, plants grown in the absence of solar UV‐B radiation (polyester) had 63 and 57% greater fresh weight and dry weight of top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
126
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(143 citation statements)
references
References 0 publications
14
126
1
2
Order By: Relevance
“…We observed a 38% reduction in total biomass production of A. sativa growing under near-ambient UV-B (Figure 1) which was mainly the result of the reduction in aboveground biomass. These results agree with other studies conducted at similar [2,7,8] and higher [10,11] latitudes. The reduction in biomass does not appear to be related to reductions in tiller or leaf production (data not shown) but rather reductions in leaf elongation (Figures 2a and 2b).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We observed a 38% reduction in total biomass production of A. sativa growing under near-ambient UV-B (Figure 1) which was mainly the result of the reduction in aboveground biomass. These results agree with other studies conducted at similar [2,7,8] and higher [10,11] latitudes. The reduction in biomass does not appear to be related to reductions in tiller or leaf production (data not shown) but rather reductions in leaf elongation (Figures 2a and 2b).…”
Section: Discussionsupporting
confidence: 83%
“…Plant responses to UV-B tend to be subtle and species-specific, especially when studies are conducted outside under realistic spectral regimes. Responses to elevated and ambient UV-B include increases in DNA-damage and antioxidant response [2], alterations in plant morphology and architecture [3,4], slight reductions in chlorophyll fluorescence parameters associated with photosystem II [PSII; 5,6] and lower biomass accumulation [7][8][9][10][11]. The most common response of field-grown plants to elevated and ambient levels of UV-B appears to be an increase in concentrations of UV-absorbing phenolics [1,12,13] that may ameliorate potentially damaging UV-B before it reaches sensitive chromophores [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of the basal high-power solid-state lighting with the UV-A LEDs also resulted in increased leaf area and fresh and dry mass of tomato, but it decreased the growth and development of cucumber transplants (Brazaitytė et al, 2009(Brazaitytė et al, , 2010. Various studies showed a UV-A inhibition effect on plant growth in different plant species and suggested that the decrease under UV irradiation was induced by damage to the photosynthetic apparatus by damaging photosystem II (Krizek et al, 1998;Turcsányi and Vass, 2000). Our investigations revealed that supplemental UV-A irradiation had no negative effect on the chlorophyll content.…”
Section: Discussionmentioning
confidence: 99%
“…The level of such radiation is affected by changes in stratospheric ozone depletion, so most investigations have focused on UV-B (Hollósy, 2002;Zhou et al, 2007). According to literature data, UV-B reduced plant height, leaf area and length, fresh and dry biomass, and such response depends on the irradiation intensity level, environmental conditions, plant species (Krizek et al, 1998;Tsormpatsidis et al, 2008;Turcsányi and Vass, 2000). Moreover, the change in various internal plant parameters also depends on different levels of UV-B radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The oxalate data are presented in Table 1 on a WM and DM basis. The data presented on a WM basis shows the data as it would normally be eaten, while data presented on a DM basis shows the differences in oxalate accumulation between each of the three treatments as UV radiation is known to decrease biomass accumulation and yield (Kalbin et al, 2001;Krizek, Britz, & Mirecki, 1998;Mazza et al, 1999).…”
Section: Resultsmentioning
confidence: 99%